Non Core Liabilities Bank, Perannya dalam Membantu Bank Mengelola Dampak Transmisi Kebijakan Moneter melalui Jalur Kredit di Indonesia - Zharmida, Vienella; I Soesilo, Nining (Jurnal Kebijakan Ekonomi, 2023)
After the global financial crisis, Asian banks shifted funding from core to non-core liabilities. This study examines the impact of NCL on bank lending channels in Indonesia. Analyzing data from 95 banks during 2010-2019, the study finds that loose monetary policy significantly boosts loan growth, while tight policy curbs it across all banks. Higher non-core liabilities weaken lending channels, except for domestic banks. This underscores the central bank's role in using macroprudential tools to manage optimal NCL levels for banks, especially amidst financial innovations and business developments affecting future bank funding access.